Analisis Ketiadaan Kepastian Hukum bagi Masyarakat Adat dalam Proyek Strategis Nasional Guna Mendorong Revisi Kebijakan Pembangunan Nasional Berdasarkan Prinsip Pluralisme Hukum - Muhammad Mujab Nabil; Zahran Qolbi Salim; Amelia Nabila Pramesthi; Ianju Parlindungan Tinambunan (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2025)
The National Strategic Projects (PSN) launched by the Indonesian government aim to accelerate development and drive national economic growth. However, in practice, many of these projects overlap with customary territories that lack formal legal certainty. This legal uncertainty gives rise to various problems, such as agrarian conflicts, criminalization of indigenous peoples, and the loss of living space and cultural identity of local communities. This study aims to analyze the forms of legal uncertainty experienced by indigenous peoples in the implementation of PSN and its impact on the protection of their collective rights. Additionally, this study explores the relevance of the principle of legal pluralism as a normative foundation for reforming national development policies to be more inclusive and ensure legal certainty for indigenous peoples. The approach used is normative qualitative with a literature study of regulations, court decisions, and reports from civil society organizations. The results of the analysis show that the legal imbalance between state law and customary law is the root cause of the marginalization of indigenous peoples in large-scale national development projects. The principle of legal pluralism, which recognizes the existence of customary law as a legitimate legal system, can be an alternative approach in formulating future development policies. The application of legal pluralism enables the state to build a development model based on social justice, participation, and respect for legal and cultural diversity. Thus, policy reform based on legal pluralism is an urgent necessity in addressing the challenges of structural justice for indigenous communities amid the tide of national development.